Biomineralization of 2′2′4′4′-Tetrabromodiphenyl ether in a Pseudomonas putida and Fe/Pd nanoparticles integrated system. (April 2019) - Jia, Yating; Hu, Fan; Lv, Yuancai; Chen, Yuancai; Hu, Yongyou
Abstract: Polybrominated diphenyl ethers (PBDEs) are widely used as flame retardants and challenges for water treatment due to their persistence and toxicity. In this study, the reduction of 2′2′4′4′-tetrabromodiphenyl ether (BDE-47) was investigated in a nano-bio-integrated system. Results showed that the introducing of P. putida could markedly accelerate the demineralization of BDE-47 in nZVI/Pd- P.p system; the continuous generation of acidic metaboliates by P. putida could decrease pH, which could alleviate the surface passivation to some extent, resulting in the releasing of Fe 2+ and high generation of H2 O2, the shift in reactive oxygen species from Fe(IV) to OH. The BDE-47 was firstly debrominated to the DE by the highly reductive [Pd·2H] generated by nZVI/Pd, then oxidized to bromophenol and phenol, catechol as well as hydroquinone via the P. putida strain and the Fenton-like system. The toxicity assays confirmed the combined system could avert generation of nocuous intermediates, and could be an alternative strategy for complete remediation of recalcitrant POPs. Graphical abstract: Image 1 Highlights: An integration of nZVI/Pd particles and P. putida (nZVI/Pd- P.p) was constructed to remove BDE-47 in a single reactor. BDE-47 could achieve rapid and nearly complete mineralization in aerobic nZVI/Pd- P.p system. The degradation kinetics and pathways of BDE-47 by nZVI/Pd- P.p in anoxic and aerobic cases were discussed and compared. The synergy reaction in the aerobic nZVI/Pd- P.p system was verified.